Zinc and iron adequacy and relative importance of zinc/iron storage and intakes among breastfed infants - Oraporn Dumrongwongsiri; Pattanee Winichagoon; Nalinee Chongviriyaphan; Umaporn Suthutvoravut; Veit Grote; Berthold Koletzko (Wiley, 2022)
Abstract Neonatal nutrient storage and supplies from breast milk contribute to nutrient status and growth of infants during their early life. This study investigated the adequacy of zinc and iron intakes among breastfed infants during the first 4 months and determined the relative importance of zinc/iron storage versus nutrient intakes with infant's biochemical status and growth. A longitudinal study followed lactating women and their breastfed infants from birth to 4 months postpartum. Cord zinc and ferritin concentrations, as indicators of nutrient storages, were determined. Zinc and iron intakes from breast milk were determined by measurement of breast milk volume together with milk zinc and iron concentrations at 2 and 4 months postpartum. Inadequacy of nutrient intakes was determined using average requirement (AR) which were 1.6 and 0.24 mg/day for zinc and iron respectively. Infant's serum zinc and ferritin were determined at 4 months of age. The data were collected from 64 and 56 participants at 2 months and 4 months postpartum. Inadequate zinc intake was found in 14.5 and 40% of infants at 2 and 4 months old, respectively. The prevalence of biochemical zinc and iron deficiency in infants were 76 and 11%, respectively. Iron endowment was significantly associated with serum ferritin at 4 months. The cumulative zinc intake was positively associated with weight gain and weight‐for‐length Z‐score, but not length. This study provides quantitative data on zinc and iron intakes, and demonstrates the relative importance of nutrient storage versus intakes on biochemical status and growth of breastfed infants.